The bounds of suicide talk: Implications for qualitative suicide research. (January 2022) - Ranahan, Patti; Keefe, Veronica
Following the implementation of a provincial suicide prevention gatekeeper training initiative in western Canada between 2015 and 2018, we conducted a focused ethnography designed to capture the post-initiative context within one small community. Analyses of our field observations and interviews with community members suggest suicide prevention work is represented in multiple informal or coordinated actions to generate innovative pathways to provoke open conversations about suicide. Simultaneously, suicide talk is constrained and managed to limit vulnerability and exposure and adhere to community privacy norms. Further, parameters around suicide talk may be employed in efforts to construct the community and mental health care in livable ways. As the research process paralleled existing representations of suicide prevention work in the community, this paper explores our entanglement in the bounds of suicide talk during phases of recruitment, data collection and knowledge translation activities.